KEBEBASAN DAN KEMANDIRIAN BADAN PEMERIKSA KEUANGAN DALAM PENGAWASAN PENGGUNAAN KEUANGAN NEGARA BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Fery Aferio; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Management and financial responsibility of the State plays an important role in realizing the goal state, so that the founding fathers felt the need to form a special state institution which is independent, objective and free from the influence of the government to examine how the government uses the state budget approved by the House of Representatives ( DPR), such institution is the State Audit Board (BPK). One of the institutions of the State in the Constitution of the Republic of Indonesia Year 1945 is the State's financial supervisory powers stipulated in the Constitution of the Republic of Indonesia Year 1945, in article 23, letter e (1) states